#TITLE_ALTERNATIVE# - DIAMOND (NIM : 12208049), IOTA
Tight gas reservoir is one of unconventional hydrocarbon sources. Permeability in tight gas reservoir is really poor with the result that fluid cannot be produced naturally and economically. To develop this reservoir, technology such as hydraulic fracturing is needed to increase permeability in order to increase the flow rate. The purpose of this study is to obtain the dimensionless IPR equation for vertical hydraulically fractured dry gas well in tight gas reservoir with square drainage area. Generally, IPR equation can be obtained when the pressure drawdown has affected every reservoir boundary, that is when the production has reached pseudo steady state period. However, in tight gas reservoir, it needs a long time Ã‚Â–around five to ten years to reach the pseudo steady state period whereas the reservoir deliverability needs to be known at every time. Therefore, in this study, a dimensionless IPR equation that can be used in transient period when pseudo steady state period has not be reached yet will be determined. Tight gas reservoir modelling with square drainage area is modeled using PETREL and ECLIPSE simulator. Validation is finished using volumetric equation for gas reservoir and volumetric equation and type curve matching using Ecrin software. Variables that are used for sensitivity in this study are fracture length and fracture height. The expected result is one dimensionless IPR equation for different values in each variable.